Ações de mediação na apropriação da linguagem escrita: análise da prática docente - Saraiva, Mônica de Araújo (2013)
The understanding of man as a social and historical subject guides to the need to analyze the work with writing in literacy classes language, designing the language from its historical, dialogical, social and cultural character. Under this understanding, the teacher plays the role of mediator vehicle, leaving him teach, challenge and encourage his student, aiming their learning and development. From this perspective, working with speech genres, a basic tool in this process, represents a great challenge for the teaching practice, requiring, from the teacher, a posture that allows the student acquires the written language and, concomitantly, social practices mediated by written. In this context, forward the studies and articulations with the Project Continuing Education for Teachers of Basic Education in the early years research: actions for Cities Administrations with Low Literacy IDEB of Western Paraná, the Post-graduate studies in Literature State University of West Paraná (UNIOESTE), linked to CAPES / INEP, through the Centre for Education Program, we were motivated to broaden the discussion about the topic inherent acquires the written language, to analyze the contribution of the actions of the mediation teacher in working with speech genres in classes in the literacy process. Guided by the question - how the actions of the mediation teacher, while working with speech genres in the literacy process, can contribute to the appropriation of writing students from 2nd year of primary school language? It went in search of answer (s). In this perspective, this research was guided from the following general objective: to analyze the pedagogical practice with a view to identifying actions to mediate the appropriation of the written language. Looking the carried through this investigative purpose, we have developed a qualitative research, ethnographic type, supported by the methodology of action research, as we propose the analyze the production and rewriting texts by working with the speech genres in a class of 2nd year Teaching Fundamentally, in which, as a teacher, mediate actions involving individual production practices and rewriting, and collective, texts and genres invitation and fairy tale. It is, therefore, a search focused on Applied Linguistics, supported the assumptions of Historical-Cultural Psychology and Socio-Historical Conception of Language. The investigative process allowed us to evaluate and analyze our actions in this work, highlighting its contribution to the learning of the students. The results reveal the necessity of our action on mediation and intervention in the face of activities that promote the appropriation of the written language. As more experienced subjects, we can provide, the student, understanding the social uses of writing and its organizational structure, increasing its ability to act with language in different contexts of dialogue